2017
DOI: 10.5527/wjn.v6.i3.100
|View full text |Cite
|
Sign up to set email alerts
|

Role of different imaging modalities of vascular calcification in predicting outcomes in chronic kidney disease

Abstract: Vascular calcification (VC) is common among patients with chronic kidney disease (CKD). The severity of VC is associated with increased risk of cardiovascular events and mortality. Risk factors for VC include traditional cardiovascular risk factors as well as CKD-related risk factors such as increased calcium and phosphate load. VC is observed in arteries of all sizes from small arterioles to aorta, both in the intima and the media of arterial wall. Several imaging techniques have been utilized in the evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 107 publications
(98 reference statements)
0
21
0
1
Order By: Relevance
“…Few studies have analyzed the effects of the progression of AAC assessed by lateral lumbar radiography among HD patients. Although a CT scan is the most sensitive and accurate technique for evaluating VC [40], we assumed that this semi-quantitative method also offers acceptable sensitivity and specificity as a useful alternative to a CT scan [18]. AAC in patients on chronic HD reflects the severity of atherosclerosis and correlate with calcification at other sites [41].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have analyzed the effects of the progression of AAC assessed by lateral lumbar radiography among HD patients. Although a CT scan is the most sensitive and accurate technique for evaluating VC [40], we assumed that this semi-quantitative method also offers acceptable sensitivity and specificity as a useful alternative to a CT scan [18]. AAC in patients on chronic HD reflects the severity of atherosclerosis and correlate with calcification at other sites [41].…”
Section: Discussionmentioning
confidence: 99%
“…The optimum diagnostic technique for vascular calcification remains unsettled. CT based imaging is outstanding in accuracy and reproducibility, yet plain radiography is a convenient and inexpensive alternative, and it delivers substantially lower radiation [28]. The predictive value of AACS based on lateral lumbar X-ray film for CVD and mortality has been validated in the general population [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography is a cost-effective and sensitive method for the detection of VC in the peripheral arteries, such as the carotid artery or radial artery. 16 Abbreviation: ABI, ankle brachial index. * The ABI was evaluated preoperatively; the results showed that the more pathologic the ABI, the more challenging the anastomosis (grade from 1 [very straightforward] through 5 [very difficult]; P < .001; likelihood ratio, 36.978).…”
Section: Discussionmentioning
confidence: 99%